O meio ambiente de trabalho em tempos de desenvolvimento: a aplicação das convenções nº 148, 161 e 167 da OIT no caso Belo Monte - GONÇALVES, Caio César Gadelha Moreira (Universidade Federal do Pará, 2017)
The paradigmatic transition of the enforcement of labor rights related to employee health offers circumstances in which the law is still reluctant to comply with them. This article analyzes the impacts of internationalization of International Labor Conventions n. 148, 161 and 167, coming from the International Labor Organization and what changes are necessary to the working environment in the Brazilian legal system. The problem of this work rests on the use of market asymmetries for the construction of large development projects, executed at any cost. The work has as background the internalization of the ILO conventions as legal innovation necessary to overcome the chronic conditions of violations to the work environment. The use of these instruments strengthens a new juridical rationality, in view of the problematic that occurs when taking into account the social complexity, since these international instruments must be used to break with the internal legal factors that do not offer the solution of this factual picture. Lastly, it was examined what are the reflexes by inserting these international documents from the new legal rationality that serves as a parameter of evolution so that the Internal Law can follow the phenomenon of the International Protection of Human Rights.